Freedom through Submission: Muslim-talk in Contemporary Denmark - Renders, Johannes, (Muslim Minorities ;, 2021)
"In Freedom through Submission Johannes Renders explores Danish-Muslim statements on human freedom. Within a context where public talk of Islam is largely mediated by an incessant succession of controversies, the notion of freedom is weaponized both by and against a growing Muslim community. Danish Muslims take issue with liberal associations of the notion with autonomy and choice, and seek to reconfigure the public debate that pits freedom against Islam. This book brings out a sophisticated and reflective Muslim discourse, in which freedom is something individuals must simultaneously exercise, surrender, and achieve in a cultivated relinquishing of the will to Allah"--